2015
DOI: 10.1002/2014ja020631
|View full text |Cite
|
Sign up to set email alerts
|

Are steady magnetospheric convection events prolonged substorms?

Abstract: Magnetospheric modes, including substorms, sawtooth events, and steady magnetospheric convection events, have in the past been described as different responses of the magnetosphere to coupling with the solar wind. Using previously determined event lists for sawtooth events, steady magnetospheric convection events, and substorms, we produce a statistical study of these event types to examine their similarities and behavior in terms of solar wind parameters, auroral brightness, open magnetospheric flux, and geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 36 publications
12
59
0
Order By: Relevance
“…Walach and Milan [] also found a similar change in IMF B z (without time shift) just prior to the sawtooth injection time (by ~ 25 min). If the epoch (injection) times in Walach and Milan [] can be measured by the Dst times, then their Figure also shows an average AE (= AU − AL ) that peaks at ~ 800 nT at ~ 2 h before the epoch and decreases afterward, consistent with our results of AE conditions for Ψ during and Ψ after (see Table ).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Walach and Milan [] also found a similar change in IMF B z (without time shift) just prior to the sawtooth injection time (by ~ 25 min). If the epoch (injection) times in Walach and Milan [] can be measured by the Dst times, then their Figure also shows an average AE (= AU − AL ) that peaks at ~ 800 nT at ~ 2 h before the epoch and decreases afterward, consistent with our results of AE conditions for Ψ during and Ψ after (see Table ).…”
Section: Discussionsupporting
confidence: 76%
“…We should note here that the elevated V sw (> 500 km s − 1 ) on average for Ψ after seems to be somewhat inconsistent with the result of Walach and Milan [], who found such elevated V sw condition to be related to the occurrences of sawteeth, instead. Although the histogram for V sw in Figure does show that l = 4 occurs about 30% of the times during sawtooth intervals, this condition is only the second most probable V sw condition during STE intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2.4. In the case where dayside and nightside reconnection occur together, steady magnetospheric convection can ensue (e.g., Sergeev et al 1996;Walach and Milan 2015). In the substorm of Fig.…”
Section: Substormsmentioning
confidence: 99%
“…The reason why the steady state is mostly achieved during active intervals (except for northward IMF quiet-time conditions) still needs to be explained. Recently, Walach et and Milan (2015) showed that a large fraction of SMCs can be viewed as "driven expansion phases", i.e. where the IMF remains southwards for a prolonged time interval after substorm onset.…”
Section: Introductionmentioning
confidence: 99%